For when bacterial infections persist: Toll‐like receptor‐inducible direct antimicrobial pathways in macrophages. Issue 1 (3rd January 2018) - Stocks, Claudia J.; Schembri, Mark A.; Sweet, Matthew J.; Kapetanovic, Ronan
Abstract: Macrophages are linchpins of innate immunity, responding to invading microorganisms by initiating coordinated inflammatory and antimicrobial programs. Immediate antimicrobial responses, such as NADPH‐dependent reactive oxygen species (ROS), are triggered upon phagocytic receptor engagement. Macrophages also detect and respond to microbial products through pattern recognition receptors (PRRs), such as TLRs. TLR signaling influences multiple biological processes including antigen presentation, cell survival, inflammation, and direct antimicrobial responses. The latter enables macrophages to combat infectious agents that persist within the intracellular environment. In this review, we summarize our current understanding of TLR‐inducible direct antimicrobial responses that macrophages employ against bacterial pathogens, with a focus on emerging evidence linking TLR signaling to reprogramming of mitochondrial functions to enable the production of direct antimicrobial agents such as ROS and itaconic acid. In addition, we describe other TLR‐inducible antimicrobial pathways, including autophagy/mitophagy, modulation of nutrient availability, metal ion toxicity, reactive nitrogen species, immune GTPases (immunity‐related GTPases and guanylate‐binding proteins), and antimicrobial peptides. We also describe examples of mechanisms of evasion of such pathways by professional intramacrophage pathogens, with a focus on Salmonella, Mycobacteria, and Listeria . An understanding of how TLR‐inducible direct antimicrobial responses are regulated, as well as how bacterial pathogens subvert such pathways, may provide new opportunities for manipulating host defence to combat infectious diseases.